2023
DOI: 10.2196/46715
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Video Call–Based Telehealth in Allied Health Professions and Nursing: Scoping Review and Mapping Process

Abstract: Background Telehealth interventions have become increasingly important in health care provision, particularly during the COVID-19 pandemic. Video calls have emerged as a popular and effective method for delivering telehealth services; however, barriers limit the adoption among allied health professionals and nurses. Objective This review aimed to identify and map the perceived barriers to the use of video call–based telehealth interventions among allied… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…This low proportion of those reporting a high skill level in our study could explain the study results of barriers reported by healthcare workers, such as lack of training that ranked as the first barrier, followed by connection problems and unavailability of the tools. Several studies had similar results in various healthcare settings and approaches, such as home care, 54 mental health, 55 allied health, the nursing profession, 56 and various clinical settings. 36 PHC workers’ leading suggestions were more TM training and stabilization of connection and networking signals.…”
Section: Discussionmentioning
confidence: 79%
“…This low proportion of those reporting a high skill level in our study could explain the study results of barriers reported by healthcare workers, such as lack of training that ranked as the first barrier, followed by connection problems and unavailability of the tools. Several studies had similar results in various healthcare settings and approaches, such as home care, 54 mental health, 55 allied health, the nursing profession, 56 and various clinical settings. 36 PHC workers’ leading suggestions were more TM training and stabilization of connection and networking signals.…”
Section: Discussionmentioning
confidence: 79%
“…To successfully and sustainably implement telehealth and subsequently reap the benefits, it is necessary to integrate telehealth into the curricula of future health care providers [5]. A lack of knowledge and experience, as well as a lack of appropriate telehealth training, have been identified as major barriers to telehealth implementation among health care providers [17]. Conversely, telehealth education and training can increase the willingness to adopt telehealth, the perceived readiness, and confidence [5,13,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, no item explored the impact of technology issues on the fidelity of a telehealth intervention delivery. Recent studies, as well as our raters' comments, highlight issues with technology as important deterrents to telehealth service delivery ( De Taeye et al, 2023 ; Dostie et al, 2023 ; Grant et al, 2022 ; Hall et al, 2022 ; Hall et al, 2021 ; Kwok et al, 2022 ; Rettinger & Kuhn, 2023 ; Tully et al, 2021 ; Wittmeier et al, 2022 ). Consequently, the inclusion of behaviors related to navigating technology and/or associated with partnering with parents to resolve technological issues may need to be considered when assessing the fidelity of telehealth interventions.…”
Section: Discussionmentioning
confidence: 93%